Self-Powered Broadband Photodetector Based on NiO/Si Heterojunction Incorporating Graphene Transparent Conducting Layer - Bhishma Pandit; Bhaskar Parida; Hyeon-Sik Jang; Keun Heo (Nanomaterials, 2024)
In this study, a self-powered broadband photodetector based on graphene/NiO/n-Si was fabricated by the direct spin-coating of nanostructured NiO on the Si substrate. The current–voltage measurement of the NiO/Si heterostructure exhibited rectifying characteristics with enhanced photocurrent under light illumination. Photodetection capability was measured in the range from 300 nm to 800 nm, and a higher photoresponse in the UV region was observed due to the wide bandgap of NiO. The presence of a top graphene transparent conducting electrode further enhanced the responsivity in the whole measured wavelength region from 350 to 800 nm. The photoresponse of the NiO/Si detector at 350 nm was found to increase from 0.0187 to 0.163 A/W at −1 V with the insertion of the graphene top layer. A high photo-to-dark current ratio (≃104) at the zero bias indicates that the device has advantageous application in energy-efficient high-performance broadband photodetectors.